THE POTENCY OF KATUK LEAVES AS AN ANTIOXIDANT IN ORTHODONTICS - Herawati, Hillda; Shafira Oktaviana, Nabila; Muchtar Surya Wiguna, Randi (Journal of Health and Dental Sciences, 2024)
Katuk leaves (Sauropus androgynus L. Merr) are known for their antioxidant, anti-inflammatory, and antimicrobial properties. Orthodontic treatments often involve prolonged use of metal appliances, which can lead to oxidative stress and inflammation in the oral environment. Antioxidants are crucial in mitigating these effects, potentially improving the outcomes and comfort of orthodontic treatments. Katuk leaves, rich in antioxidants such as flavonoids, saponin, tannin, quinone, polyphenols, and vitamins, can slow down the formation of free radicals during the tooth movement process. This literature review explores the potential application of katuk leaves as a natural antioxidant in orthodontics, focusing on enhancing patient care by reducing oxidative stress and inflammation associated with orthodontic appliances. This study was conducted using a comprehensive literature review approach. Relevant keywords from articles were sourced from databases, including Google Scholar, PubMed, ResearchGate, Europe PMC, and Elsevier. Selection criteria included the year of publication, relevance to the topic, availability of abstract, full text, and alignment with the study's objectives. The review revealed evidence supporting the antioxidant effects of katuk leaves in reducing oxidative stress during tooth movement. However, there are still limitations regarding the utilization and processing of katuk leaves in clinical settings. Further research is necessary to develop standardized methods for applying katuk leaves in orthodontic treatment. Utilization of katuk leaves in orthodontic care shows the potential to enhance antioxidant levels, thereby reducing oxidative stress and improving treatment outcomes. DOI : 10.54052/jhds.v4n2.p157-170